Combined turbo detection and decoding for unknown ISI channels. - Garcia-Frias, J.
We present two decoding structures which combine turbo detection and decoding, allowing communication in the presence of intersymbol interference (ISI). The first one treats the ISI as another constituent decoder which participates in the exchange of extrinsic information, and performs slightly worse than the second structure, which combines the trellis representing each one of the constituent encoders with the ISI trellis. We show that for both methods, it is possible to obtain good performance, even when no a priori information about the ISI channel is available to the decoder.
Keywords: ISI channels; Channel estimation; Intersymbol interference; Iterative decoding; Parameter estimation; Trellis; Turbo codes; Turbo decoding; Turbo detection